2002
DOI: 10.1542/peds.110.1.e11
|View full text |Cite
|
Sign up to set email alerts
|

Can Child Deaths Be Prevented? The Arizona Child Fatality Review Program Experience

Abstract: ABSTRACT. Objective. To determine the causes and preventability of child deaths; to assess the accuracy of death certificate information; and to assess the number of child abuse deaths that are misdiagnosed as deaths attributable to natural or accidental causes.Methods. Analysis of deaths of children <18 years old that occurred between 1995-1999 using the data collected by the Arizona Child Fatality Review Program (ACFRP).Results. From 1995-1999, local multidisciplinary child fatality review teams (CFRTs) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(144 citation statements)
references
References 4 publications
8
126
2
5
Order By: Relevance
“…Portanto, o perfil de ocorrências pode variar conforme a faixa etária estudada, fonte de informação ou local pesquisado. Os autores da violência são, na maioria, familiares, compatível com o que tem sido apresentado em outros trabalhos que têm identificado os agressores como sendo o pai, o namorado ou companheiro da mãe e a própria mãe da vítima 21,22 .…”
Section: Discussionunclassified
“…Portanto, o perfil de ocorrências pode variar conforme a faixa etária estudada, fonte de informação ou local pesquisado. Os autores da violência são, na maioria, familiares, compatível com o que tem sido apresentado em outros trabalhos que têm identificado os agressores como sendo o pai, o namorado ou companheiro da mãe e a própria mãe da vítima 21,22 .…”
Section: Discussionunclassified
“…(5) Results of studies in high-income countries have consistently shown that factors can be identified in a substantial proportion of child deaths that could potentially be modified to reduce future child deaths. (21)(22)(23)(24) In New Zealand, investigators have noted the preventability of many cases of sudden unexpected death in infancy, (25) drowning, unintentional injuries, and deaths from being hit at lowspeed by motor vehicles. (8,26) The UK confidential inquiry identified avoidable factors in 31 (26%) deaths of 119 cases they reviewed, with potentially avoidable factors noted in a further 51 (43%) cases.…”
Section: Child Deaths: the Need For Actionmentioning
confidence: 99%
“…If these factors were addressed, then the accuracy of the perinatal death certificate would improve from 58% to 91%.32 In a study in Arizona, child fatality review teams examined 4806 deaths and reported basic errors in demographics in 3% of death certificates and errors in the cause of death in 13%. 22 In the UK confidential inquiry, the reviewing panels identified inaccuracies in the medical certificate of the cause of death in 33 (35%) of 95 cases.3 In two-thirds (22) of these cases, an additional diagnosis should have been included on the death certificate, in 14 of which, the missing diagnosis was considered a major, direct, or overwhelming cause of death. Panel members were most consistent in recording deaths due to malignancy, trauma, and sudden infant death, and least consistent in recording deaths reviewed as congenital or chronic medical conditions.…”
Section: Systems To Record and Classify Deathsmentioning
confidence: 99%
“…Consideram que o maior risco para afogamento é encontrado em uma piscina no quintal da casa quando um menino pequeno está sem supervisão de um adulto 38 .…”
Section: Afogamentounclassified